2016
DOI: 10.1002/best.201600051
|View full text |Cite
|
Sign up to set email alerts
|

Parabolschalen aus Hochleistungsbeton als Solarkollektoren

Abstract: Parabolrinnen in solarthermischen Kraftwerken werden bisher vornehmlich als Stahlfachwerke mit punktgestützten Spiegelelementen hergestellt. Um die Stromerzeugung kostengünstiger zu gestalten, wurde bereits an einem kleinformatigen Demonstrator mit Parabolschale gezeigt, dass solche Kollektormodule auch aus Beton hergestellt werden können [1]. Unterschiedliche Konzepte, welche sich in ihrer Apertur sowohl an etablierten Kollektormodulen mit ca. 6 m Öffnungsweite als auch an großformatigen Kollektoren mit bis z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 11 publications
0
4
0
7
Order By: Relevance
“…However, for parabolic troughs, it could be shown that slender light-weight shells made from high-performance concrete (HPC) are an economic alternative to conventional collectors due to the low costs of concrete. 7,8 HPC is characterized by a high compressive strength of approximately >70 to 80 MPa and an increased durability compared to regular concrete. 9 The findings for parabolic shell collectors are now transferred to heliostats.…”
Section: Conceptual Design Of Modular Concrete Heliostatsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for parabolic troughs, it could be shown that slender light-weight shells made from high-performance concrete (HPC) are an economic alternative to conventional collectors due to the low costs of concrete. 7,8 HPC is characterized by a high compressive strength of approximately >70 to 80 MPa and an increased durability compared to regular concrete. 9 The findings for parabolic shell collectors are now transferred to heliostats.…”
Section: Conceptual Design Of Modular Concrete Heliostatsmentioning
confidence: 99%
“…In previous designs of concrete shell collectors for parabolic troughs, the Nanodur concrete has proven to be suitable. 7,11 It exhibits good workability and has self-compacting behavior and high durability. 16 The material properties differ with respect to the used aggregates and additives.…”
Section: High-performance Concrete (Hpc)mentioning
confidence: 99%
“…Um den Schalungsaufwand für die prototypische Umsetzung vergleichsweise gering zu halten, wurde die Schale als einwandiger Vollquerschnitt ausgeführt. Ein Entwurf mit äußeren Versteifungsrippen oder innen liegenden Hohlkörpern ist zur weiteren Materialreduktion denkbar.…”
Section: Entwurf Und Randbedingungenunclassified
“…Die Schnittgrößen variieren je nach Positionierung der Schale während der Sonnennachführung. Die spezifischen Windbeanspruchungen basieren auf hinreichend genau modellierten Windkanaluntersuchungen für unterschiedliche Auslenkungen. Aufgrund des Aufstellorts des Kollektors in Borchen (Deutschland) wurde zusätzlich eine Schneelast nach berücksichtigt, welche bei typischen Standorten von solarthermischen Anlagen obsolet wäre.…”
Section: Entwurf Und Randbedingungenunclassified
“…An der TU Kaiserslautern wird seit 15 Jahren daran gearbeitet, das Trag-und Verformungsverhalten von Konstruktionen aus Hochleistungsbeton zu erforschen [11][12][13][14] und dabei auch die Vorteile von Sandwichkonstruktionen nutzbar zu machen [15,16].…”
Section: Fachthema Article 3 Entwurf Unter Verwendung Von Hochleistununclassified